The Influence Of STAD Type Learning Strategy Towards Students’ Motivation In Learning English At SMA Negeri 1 Pamona Utara - Tite, Sindi Adistika; Lantu, Ika Paramitha (Universitas Sintuwu Maroso, 2024)
This research aims to determine the influence of the STAD learning strategy on students' motivation as proven by hypothesis testing. The study uses a survey design. The research type in this study is quantitative. The population of this study are 225 and the samples are 59 students.The result of this research, it shows that STAD influences Students' Motivation 40.1%. This indicates that the null hypothesis is rejected, and the alternative hypothesis is accepted. Thus, the STAD learning strategy influences to improve learning outcomes and student enthusiasm for participating in learning ‘’ increasing students' sense of self-confidence